2022
DOI: 10.1007/s11356-022-23605-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential of bioretention plants in treating urban runoff polluted with greywater under tropical climate

Abstract: Bioretention systems are among the most popular stormwater best management practices (BMPs) for urban runoff treatment. Studies on the plant performance using bioretention systems have been conducted, especially in developed countries with a temperate climate, such as the United States and Australia. However, these results might not be applicable in developing countries with tropical climates due to the different rainfall regimes and the strength of runoff pollutants. Thus, this study focuses on the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As mentioned, plants absorb nutrients in the tissues and root system and provide space for the growth of bacteria responsible for organic degradation, so plants with relative plant growth rates and high-biomass plants are generally considered to maximize the mass of contaminants assimilated into plant biomass [12,100]. On the contrary, some studies have demonstrated that biomass production is not the most important parameter for amounts of accumulated metals.…”
Section: Linkage Between Vegetation Morphology and Adaptability To Fl...mentioning
confidence: 99%
“…As mentioned, plants absorb nutrients in the tissues and root system and provide space for the growth of bacteria responsible for organic degradation, so plants with relative plant growth rates and high-biomass plants are generally considered to maximize the mass of contaminants assimilated into plant biomass [12,100]. On the contrary, some studies have demonstrated that biomass production is not the most important parameter for amounts of accumulated metals.…”
Section: Linkage Between Vegetation Morphology and Adaptability To Fl...mentioning
confidence: 99%
“…The four most common mechanisms for removing the COD in BRCs are adsorption, filtration, microbial degradation, and plant uptake [85,92]. In particular, the adsorption mechanism is crucial because it acts as a fast capture mechanism and short-term storage reservoir, paving the way for longer-lasting processes such as biodegradation and plant uptake [127].…”
Section: Oxygen Demanding Contaminantsmentioning
confidence: 99%
“…A vegetated bioretention pilot site was planted with tropical plants, such as Red Hot Hibiscus (Hibiscus rosa-sinensis), Amaryllis (Hippeastrum), Singapore Daisy (Sphagneticola trilobata), Lobster claw (Heliconia rostrata), Alternanthera (Alternanthera cultivar). These plants have been selected according to its performance studied by Johnson et al [4]. The novelty of this study is the application of various new tropical plants in the bioretention pilot site to treat urban stormwater runoff in tropical countries, particularly Malaysia.…”
Section: Introductionmentioning
confidence: 99%